Research on lignification of post-harvested bamboo shoots by metabolomics technology - Huang, Jingsong; Zhang, Yixiang; Guo, Jun (European journal of horticultural science, 2025)
Lignification is a typical characteristic of post-harvest senescence during bamboo shoot storage, necessitating a comprehensive understanding of lignification mechanisms. To delve deeper into lignification process, key metabolites, including cinnamic acid, p-coumaric acid, ferulic acid, coniferaldehyde and sinapaldehyde, were identified and quantified using ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UPLC‒MS/MS). The findings showed that the content of coniferaldehyde (CADe) and sinapaldehyde (SAD) under low-temperature (4°C, LT) treatment was significantly higher than that under room temperature treatment (20°C, RT) during storage. The trend in cinnamic acid (Cin) content changes was in accordance with that of ferulic acid (Fer). The contents of cinnamic acid and ferulic acid under LT condition increased compared to RT, especially after 6 d of storage. In contrast, the content of p-coumaric acid (PCA) under RT was higher than that under LT throughout the entire storage period. Changes in enzyme activity related to lignin synthesis, including PAL (phenylalanine ammonia-lyase), POD (peroxidase), 4-CL (4-coumarate CoA ligase) and CAD (cinnamyl-alcohol dehydrogenase), coupled with lignin content, were assayed. The results showed LT treatment effectively suppressed enzymatic activities of PAL, POD, 4-CL and CAD during storage. In summary, LT conditioning effectively delayed post-harvest lignification of bamboo shoots by inhibiting the activity of enzymes involved in lignin synthesis and preserving a larger pool of free metabolites that would originally intend for lignin synthesis. This study provides a new perspective explaining how LT treatment can inhibit post-harvest lignification of bamboo shoots.